Analisis Financial Distress Dengan Metode ZMIJEWSKI - Desi Permatasari; Acep Samsudin; Kokom Komariah (Journal of Management and Bussines (JOMB), 2019)
This study aims to determine how the zmijewski method can be used in analyzing financial distress at PT. Jaya Konstruksi Manggala Pratama Tbk, PT. Indonesia Pondasi Raya Tbk, and PT. Mitra Pemuda Tbk. The data analysis method used is to use the zmijewski method. The results of the study, PT. Mitra Pemuda Tbk in 2015 obtained an X-Score of -0.6868 so that the company was categorized as healthy or non-distress. In 2016 PT. Mitra Pemuda obtains an X-Score value of -1,5004 and is categorized as non-distress. And in 2017 PT. Mitra Pemuda Tbk obtained the X-Score value of -1.6922 so that it was in the category of healthy or non-distress. Conclusion, PT. Jaya Konstruksi Manggala Pratama Tbk, PT. Indonesia Pondasi Raya Tbk, and PT. Mitra Pemuda Tbk based on the zmijewski method to analyze the company's third financial distress is in a healthy or non-distress condition. Keywords: Financial Distress, Financial Report, Zmijewski Method